ANALISIS LAPORAN REALISASI ANGGARAN (LRA) UNTUK MENILAI PELAKSANAAN ANGGARAN BELANJA (Studi pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Surabaya) - Anissa Bella Febriana; Maulidah Narastri (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to analyze the Budget Realization Report (LRA) to assess the implementation of the budget at the Surabaya City Financial and Regional Management Agency for the 2017-2021 fiscal year. This research was conducted at BPKAD Surabaya City. This study used descriptive qualitative method. Data collection techniques used are interviews and documentation. The data collection technique that was carried out consisted of: 1.) Analysis of the calculation of the economic level of the Budget Realization Report at the Surabaya City BPKAD for the 2017 to 2021 fiscal year 2.) Analysis of the calculation of the efficiency level of the Budget Realization Report at the Surabaya City BPKAD for the 2017 to 2021 fiscal year 3.) Analysis of the calculation of the level of effectiveness of the Budget Realization Report at the Surabaya City BPKAD for the 2017 to 2021 fiscal years. The results showed that program realization as measured by the average economic level from 2017 to 2021 was in the economic criteria and in 2019 it experienced a less economical level, the results of performance measurement as measured by the level of efficiency at the Regional Financial and Asset Management Agency for the City of Surabaya showed that inefficient and inefficient budget and performance measurement results measured by the level of effectiveness in 2017 to 2019 show very effective